The Mental Health Impact of 2019-nCOVID on Healthcare Workers From North-Eastern Piedmont, Italy. Focus on Burnout - Gramaglia, Carla; Marangon, Debora; Azzolina, Danila; Guerriero, Chiara; Lorenzini, Luca; Probo, Manuela; Rudoni, Marco; Gambaro, Eleonora; Zeppegno, Patrizia (Frontiers in Public Health, 2021)
The 2019-nCOVID pandemic as a public health emergency has faced healthcare systems with unprecedented challenges. Our study aimed to focus on the mental health impact of the 2019-nCOVID pandemic on healthcare workers (HCWs) from North-Eastern Piedmont, Italy. For this purpose, we performed an online survey which was e-mailed to HCWs at the end of the first peak of the pandemic. We involved both frontline and not-frontline HCWs, employed in the hospital or in healthcare services outside the hospital. The primary outcome of our research was the assessment of burnout, while secondary outcomes included the investigation of anxiety, depression and post-traumatic stress symptoms. We observed higher levels of burnout (especially in the Depersonalization and Personal Accomplishment dimensions), in females, in HCWs aged <30 years, in those exposed to changes in their daily and family habits, in those who had to change their duties at work and in residents in training. In our HCWs sample we found lower levels of anxiety and depression than those reported in the literature. The problematic levels of burnout and adverse psychological outcomes observed during the pandemic cannot be underestimated. Given the recurrence in autumn 2020 of a new pandemic peak, which has once again put a strain on the health system and HCWs, it is supported the importance of a careful assessment of HCWs’ mental health, and of the possible risk and protective factors both in the work environment and in the extra-work one.